Preparation method of perovskite solar cell taking alcohol-soluble SnO2 as electron transport layer, alcohol-soluble SnO2 and preparation method thereof
Through the preparation method of alcohol-soluble SnO2, the problem of limited application of SnO2 in perovskite solar cells is solved, and SnO2 nanoparticles dissolved in neutral solvents are realized for the preparation of perovskite solar cells, thereby improving photogenerating loading Flower life and device performance.
Patent Information
- Application Number
- CN202411833189.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The application of existing SnO2 materials in perovskite solar cells is limited, because moisture will destroy the perovskite structure and it is difficult to spin-coat directly in an alkaline environment, which affects the photoelectric conversion efficiency and operating life.
Alcohol-soluble SnO2 is used as the electron transport layer, and by mixing the tin salt with the solvent at 20-30°C to form a transparent SnO2 reaction solution precursor solution, then prepare nanomaterials under hydrothermal conditions and add hydroxycarboxylic acid compounds to perform Ligand exchange to obtain alcohol-soluble SnO2 nanoparticles, which are used for the preparation of perovskite solar cells.
Alcohol-soluble SnO2 can be dissolved in neutral solvents without destroying the perovskite structure, improving the life of photogenerated carriers and device performance, and enhancing the performance and life of perovskite solar cells.
Smart Images

Figure CN119306249A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solar energy technology, and specifically relates to a method for preparing a perovskite solar cell using alcohol-soluble SnO2 as an electron transport layer, alcohol-soluble SnO2 and a method for preparing the same. Background Art
[0002] With the continuous development of science and technology, perovskite solar cells have gradually attracted widespread attention as an emerging technology. In perovskite solar cells, commonly used inorganic electron transport materials mainly include TiO2 and SnO2, which are usually dispersed in water and widely used in formal device structures.
[0003] However, the application of these materials in trans structures is limited. One of the main reasons is that moisture will destroy the perovskite structure, thus narrowing their scope of use in the field of perovskite solar cells. Secondly, because in the formal device structure, SnO2 is dispersed in an alkaline aqueous solution with a pH of 11-12, it can only be used on ITO (tin-doped indium oxide) and FTO (Fluorine-doped Tin Oxide) substrates, and cannot be directly spin-coated on the perovskite layer because alkaline substances will also dissociate the perovskite, affecting its photoelectric conversion efficiency and operating life. In addition, the strong alkaline solution remaining in the SnO2 aqueous solution has high requirements for the corrosion resistance of the equipment, which further limits its application in the perovskite industry. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a perovskite solar cell using alcohol-soluble SnO2 as an electron transport layer, alcohol-soluble SnO2 and its preparation method, so as to solve the problem of limited application of SnO2 materials in perovskite solar cells in the prior art.
[0005] The technical solution adopted by the present invention is as follows: The preparation method of alcohol-soluble SnO2 comprises: S1. At 20-30°C, a tin salt is mixed with a first solvent to form a first reaction system, a ligand is mixed with a second solvent to form a second reaction system, the second reaction system is added dropwise to the first reaction system, and heated and dissolved at 50-60°C under vacuum conditions to obtain a transparent SnO2 reaction liquid precursor solution; S2. The SnO2 reaction liquid precursor solution is loaded into a hydrothermal reactor, the temperature is set at 90-200 ° C, the reaction is 1-24h, and the SnO2 nanomaterial mother solution is obtained; S3. The mother liquor of SnO2 nanomaterial is mixed with a precipitant to form a precipitate, which is then dissolved with a good solvent, precipitated with a precipitant, and the SnO2 nanoparticles are separated by centrifugation, and the washing is repeated to obtain pure SnO2 nanoparticles; S4. The SnO2 nanoparticles in S3 are dispersed with an organic alcohol, and a hydroxycarboxylic acid compound having a carbon chain number of 2-9 is added for ligand exchange, and the reaction is carried out for 1-24 hours, and the alcohol-soluble SnO2 nanoparticles are obtained after purification; S5. Dispersing SnO2 nanoparticles in an organic alcohol solvent to obtain an alcohol-soluble SnO2 dispersion.
[0006] Furthermore, the ligand in S1 is an organic amine with a carbon chain number of 6-18, an organic acid, and an organic amine with a hydroxyl group.
[0007] Furthermore, the first solvent described in S1 refers to a solvent whose boiling point is lower than the reaction temperature of the system, and the second solvent refers to a solvent whose boiling point is higher than the reaction temperature of the system.
[0008] Furthermore, in S1, the ratio of the tin salt to the ligand is 1:(0.1-10) in terms of the amount of substance.
[0009] Furthermore, the precipitant in S3 is one of methanol, ethanol, acetone and acetonitrile.
[0010] Furthermore, the good solvent in S3 is one of dichloromethane, chloroform, n-hexane, n-heptane, n-octane, toluene and xylene.
[0011] Alcohol-soluble SnO2, including SnO2 inorganic matter and organic ligands on the surface of SnO2 inorganic matter.
[0012] Furthermore, the organic ligand is a hydroxycarboxylic acid compound with a carbon chain number of 2-9, and the weight of the organic ligand accounts for 3%-25% of the whole.
[0013] Furthermore, the alcohol-soluble SnO2 has a particle size of 3-10 nm and a band gap of 3.6-4.0 eV.
[0014] The preparation method of a perovskite solar cell using alcohol-soluble SnO2 as an electron transport layer is as follows: first, a hole transport material is spin-coated on the IT0 anode layer to form a hole transport layer, a perovskite solution is spin-coated on the hole transport layer as a carrier to form an absorption layer, an alcohol solution of SnO2 is spin-coated on the absorption layer, and an electron transport layer is formed after drying, and finally an Au cathode electrode layer is evaporated and packaged to form a perovskite solar cell.
[0015] The beneficial effects of the present invention are as follows: The SnO2 provided by the present invention can be dissolved in organic alcohol solvents. These solvents (such as isopropanol) will not destroy the perovskite structure, and the pH value of the system is close to neutral, so that it can be used in perovskite devices as an electron transport layer material.
[0016] The present invention selects short-chain hydroxycarboxylic acid as an organic ligand on the surface of tin oxide, providing a relatively stable, highly conductive, low boiling point, and easily removable ligand; utilizing the chelation effect of carboxyl (-COOH) to form a stable coordination bond with SnO2, effectively reducing the dangling bonds (Sn dangling bonds and O dangling bonds) on the surface of SnO2, increasing the lifetime of photogenerated carriers in the device, and thus improving the device performance and lifetime. The hydrothermal method prepares SnO2 nanoparticles with high crystallinity and small particle size, which has fewer defect states than SnO2 prepared by the conventional low-temperature sol method, which is conducive to improving device performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 (a) is a schematic diagram of dangling bonds on the surface of conventional SnO2 nanomaterials, and (b) is a schematic diagram of ligands on the surface of modified SnO2 nanomaterials.
[0018] Figure 2 This is a TEM image (Transmission Electron Microscope image) of SnO2 nanoparticles prepared in the present invention.
[0019] Figure 3 This is the XRD pattern (X-Ray Diffraction pattern) of SnO2 nanoparticles prepared in the present invention. DETAILED DESCRIPTION
[0020] The present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0021] The present invention provides a method for preparing a perovskite solar cell using alcohol-soluble SnO2 as an electron transport layer, an alcohol-soluble SnO2 dispersion and a preparation method thereof. The perovskite solar cell comprises a transparent anode, a hole transport layer, a perovskite absorption layer, an electron transport layer and a cathode layer. The electron transport layer is prepared by spin coating, printing and slit coating of an alcohol-soluble SnO2 dispersion.
[0022] The preparation method of alcohol-soluble SnO2 comprises the following steps: S1. At 20-30°C, a tin salt is mixed with a first solvent to form a first reaction system, a ligand is mixed with a second solvent to form a second reaction system, the second reaction system is added dropwise to the first reaction system, and heated and dissolved at 50-60°C under vacuum conditions to obtain a transparent SnO2 reaction liquid precursor solution; S2. The SnO2 reaction liquid precursor solution is loaded into a hydrothermal reactor, the temperature is set at 90-200 ° C, the reaction is 1-24h, and the SnO2 nanomaterial mother solution is obtained; S3. The mother liquor of SnO2 nanomaterial is mixed with a precipitant to form a precipitate, which is then dissolved with a good solvent, precipitated with a precipitant, and separated by centrifugation to obtain SnO2 nanoparticles. The washing is repeated twice to obtain pure SnO2 nanoparticles. S4. The SnO2 nanomaterial in S3 is dispersed with an organic alcohol solution, a hydroxycarboxylic acid compound having a carbon chain number of 2-9 is added for ligand exchange, the reaction is carried out for 1-24 hours, and alcohol-soluble SnO2 nanoparticles are obtained after purification; S5. Dispersing SnO2 nanoparticles in an organic alcohol solvent to obtain an alcohol-soluble SnO2 dispersion.
[0023] The particle size of SnO2 nanomaterials is determined by the temperature and reaction time of the hydrothermal reaction. Generally speaking, the higher the temperature and the longer the time, the larger the particle size of the nanomaterials will be. The photoelectric properties of nanomaterials are related to the particle size. The device performance of 5-10nm SnO2 is the best.
[0024] The tin salt described in S1 can be selected from but is not limited to SnCl4 and its pentahydrate, SnCl2 and its dihydrate, tin (II) sulfate, tin acetate, tin trifluoromethanesulfonate, tin tetrafluoride, stannous isooctanoate, tin tetraiodide, butyltin trichloride, tin tetrabromide, dibutyltin oxide, stannous iodide, tin (II) bromide, tin (II) oxalate, tin diacetylacetonate, tin diacetylacetonate chloride, sodium stannate and its compounds, tin ethoxide, dibutyltin dichloride, stannous tetrafluoroborate, dibutyltin diacetate, butyltin tri(2-ethyl-1-hexanoate), potassium stannate (IV) and its trihydrate, monobutyltin trichloride, and one or more of trimethyltin chloride.
[0025] The ligand described in S1 is selected from organic amines, organic acids, and organic amines with hydroxyl groups having a carbon chain number of 6-18, wherein the organic amine can be selected from but not limited to one or more of n-hexylamine, n-octylamine, n-decylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, n-octadecylamine, and oleylamine; the organic acid can be selected from but not limited to one or more of n-hexanoic acid, n-octanoic acid, n-decanoic acid, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, n-octadecylamine, and oleic acid; the amines with hydroxyl groups can be selected from but not limited to one or more of ethanolamine, diethanolamine, triethanolamine, and isopropanolamine.
[0026] The first solvent described in S1 refers to a solvent whose boiling point is lower than the reaction temperature of the system, which is used to form high pressure conditions; it can be selected from but not limited to the following: water, methanol, ethanol, isopropanol; The second solvent described in S1 refers to a solvent whose boiling point is higher than the reaction temperature of the system, and can be selected from but not limited to the following substances: water, dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidone (NMP) and monohydric alcohols with a boiling point of 100-250°C, such as n-butanol, tert-butanol, isopentanol, n-pentanol, isohexanol, n-hexanol, n-heptanol, n-octanol, n-nonanol, n-decanol, benzyl alcohol, and phenylethyl alcohol; The hydroxycarboxylic acid compound with 2 to 9 carbon chains described in S4 satisfies the following general formula: HO-R-COOH, where R can be an alkyl group (R-) or an aryl group (Ar-); For example, the alkyl group may be selected from but not limited to one or more of glycolic acid, propanoic acid, caproic acid, isopropanoic acid, and isohexanoic acid; for example, the aryl group may be selected from but not limited to one or more of benzoic acid, phenylacetic acid, and phenylpropionic acid.
[0027] The organic alcohol solvent may be selected from but is not limited to one or more mixed solvents of ethanol, methanol, isopropanol, n-butanol, and isobutanol.
[0028] The present invention also provides an alcohol-soluble SnO2 dispersion, wherein the alcohol-soluble SnO2 comprises SnO2 inorganic matter and organic ligands on the surface of SnO2, and the band gap range is calculated to be 3.6-4.0 eV.
[0029] The surface of the nanoparticles carries the hydroxycarboxylic acid ligands of the present application, which, on the one hand, disperse SnO2 in alcohol organic solvents; on the other hand, they coordinate with the dangling bonds in SnO2 to reduce the defect states in SnO2, thereby increasing the lifetime of photogenerated carriers and improving device performance and lifetime.
[0030] The weight of ligands on the surface of nanoparticles accounts for 3%-25% of the total weight. The calculation method is based on thermogravimetric analysis, which is the percentage of thermal weight loss of nanomaterial powder in the temperature range of 100-600°C.
[0031] The electron mobility of the nanomaterials described in the present invention is between 10 and 200 cm 2 V -1 s -1 between.
[0032] The present invention also provides an inverted perovskite solar cell structure, namely a transparent anode, a hole transport layer, a perovskite absorption layer, an electron transport layer, and a cathode layer. The electron transport layer is prepared by spin coating, printing, and slit coating processes using the alcohol-soluble tin oxide dispersion in the present application.
[0033] A method for preparing alcohol-soluble SnO2 comprises the following steps: Embodiment 1 S1. At room temperature, 1mmol SnCl4・5H2O was mixed with 50ml ethanol to form a first reaction system, 1mmol ethanolamine, 1mmol n-hexylamine, 2mmol n-hexanoic acid and 50ml DMF were mixed to form a second reaction system, the second reaction system was added dropwise to the first reaction system, and heated and dissolved at 100pa and 60°C to obtain a transparent SnO2 reaction liquid precursor solution; S2. The SnO2 reaction liquid precursor solution was loaded into a 200ml hydrothermal reactor, the temperature was set at 120°C, and the reaction was carried out for 3h to obtain a SnO2 nanomaterial mother liquor; S3. The SnO2 nanomaterial mother liquor was mixed with 500ml of methanol, centrifuged to obtain a precipitate, and then dissolved with 50ml of n-hexane, 100ml of methanol was added to precipitate, and the SnO2 nanoparticles were separated by centrifugation at 5000rpm, and the washing was repeated twice to obtain pure SnO2 nanoparticles; S4. Disperse SnO2 nanoparticles in 100 ml of isopropanol, add 1 g of isopropanoic acid, react for 2 h, and precipitate with 200 ml of n-hexane to obtain alcohol-soluble SnO2 nanoparticles.
[0034] S5. Disperse SnO2 nanoparticles in isopropanol to obtain a 2.5 wt% isopropanol SnO2 dispersion.
[0035] Embodiment 2 S1. At room temperature, 1 mmol of tin acetate was mixed with 50 ml of ethanol to form a first reaction system, 0.5 mmol of ethanolamine, 1 mmol of oleic acid, 0.5 mmol of oleylamine and 80 ml of DMSO were mixed to form a second reaction system, the second reaction system was added dropwise to the first reaction system, and heated and dissolved at 100 Pa, 60 ° C to obtain a transparent SnO2 reaction liquid precursor solution; S2. The SnO2 reaction liquid precursor solution was loaded into a 200ml hydrothermal reactor, the temperature was set at 150 ° C, and the reaction was carried out for 2h to obtain a SnO2 nanomaterial mother solution; S3. The SnO2 nanomaterial mother liquor was mixed with 500ml of ethanol, centrifuged to obtain a precipitate, and then dissolved with 50ml of n-heptane, 100ml of ethanol was added to precipitate, and the SnO2 nanoparticles were separated by centrifugation at 5000rpm, and the washing was repeated twice to obtain pure SnO2 nanoparticles; S4. Disperse SnO2 nanoparticles in 100 ml of isopropanol, add 2 g of p-hydroxyphenylacetic acid, react for 5 h, and precipitate with 200 ml of n-heptane to obtain alcohol-soluble SnO2 nanoparticles.
[0036] S5. Disperse SnO2 nanoparticles in isopropanol to obtain a 2.5 wt% isopropanol SnO2 dispersion.
[0037] Embodiment 3 S1. At room temperature, 1mmol SnCl2・2H2O was mixed with 50ml tert-butanol to form a first reaction system, 1mmol diethanolamine, 1mmol n-dodecylamine, 2mmol n-dodecanoic acid and 50ml ethanol were mixed to form a second reaction system, the second reaction system was added dropwise to the first reaction system, and heated and dissolved at 100pa, 60℃ to obtain a transparent SnO2 reaction liquid precursor solution; S2. The SnO2 reaction liquid precursor solution was loaded into a 200ml hydrothermal reactor, the temperature was set to 180 ° C, and the reaction was carried out for 3h to obtain a SnO2 nanomaterial mother solution; S3. The SnO2 nanomaterial mother liquor was mixed with 500ml of acetone, centrifuged to obtain a precipitate, and then dissolved with 50ml of n-octane, 100ml of acetone was added to precipitate, and the SnO2 nanoparticles were separated by centrifugation at 5000rpm, and the washing was repeated twice to obtain pure SnO2 nanoparticles; S4. The SnO2 nanoparticles were dispersed in 100 ml of isopropanol, 3 g of hydroxycaproic acid was added, the reaction was continued for 10 h, and precipitated with 200 ml of n-heptane to obtain alcohol-soluble SnO2 nanoparticles; S5. Disperse SnO2 nanoparticles in isopropanol to obtain a 2.5 wt% isopropanol SnO2 dispersion.
[0038] The electron transport layer of the device is made from the tin oxide isopropanol dispersion in the embodiment and applied to the inverse perovskite solar cell. The inverse perovskite solar cell includes an ITO anode, a NiO x Hole transport layer, perovskite absorption layer, tin oxide electron transport layer and cathode gold.
[0039] The preparation method of an inverse perovskite solar cell comprises the following steps: spin coating an aqueous solution of nickel oxide on an IT0 anode layer, and then annealing at 100° C. for 10 min to form a hole transport layer; spin coating a perovskite solution on the hole transport layer as a carrier to form an absorption layer; spin coating the tin oxide isopropanol dispersion in Example 1 on the absorption layer, and forming an electron transport layer after drying; and finally evaporating an Au cathode electrode layer and encapsulating to form a perovskite solar cell device.
[0040] Inkjet printing method: In the above spin coating method, only the spin coating process is changed to inkjet printing, and the tin oxide layer material is annealed by a gradient temperature increase method under high vacuum conditions.
[0041] Comparative Example 1 S1. The 1mmol tin tetrachloride pentahydrate was dissolved in 500ml of deionized water, 10% NaOH aqueous solution was added, the pH was controlled at 12, and stirred until transparent to obtain SnO2 nanomaterial mother liquor; S2. Add hydrochloric acid to the mother liquor to precipitate SnO2, centrifuge to obtain SnO2 nanoparticles, and then disperse them in deionized water to obtain SnO2 aqueous dispersion.
[0042] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A method for preparing alcohol-soluble SnO2, characterized in that: include: S1. At 20-30°C, a tin salt is mixed with a first solvent to form a first reaction system, a ligand is mixed with a second solvent to form a second reaction system, the second reaction system is added dropwise to the first reaction system, and heated and dissolved at 50-60°C under vacuum conditions to obtain a transparent SnO2 reaction liquid precursor solution; S2. The SnO2 reaction liquid precursor solution is loaded into a hydrothermal reactor, the temperature is set at 90-200 ° C, the reaction is 1-24h, and the SnO2 nanomaterial mother solution is obtained; S3. The mother liquor of SnO2 nanomaterial is mixed with a precipitant to form a precipitate, which is then dissolved with a good solvent, precipitated with a precipitant, and the SnO2 nanoparticles are separated by centrifugation, and the washing is repeated to obtain pure SnO2 nanoparticles; S4. The SnO2 nanoparticles in S3 are dispersed with an organic alcohol, and a hydroxycarboxylic acid compound having a carbon chain number of 2-9 is added for ligand exchange, and the reaction is carried out for 1-24 hours, and the alcohol-soluble SnO2 nanoparticles are obtained after purification; S5. Dispersing SnO2 nanoparticles in an organic alcohol solvent to obtain an alcohol-soluble SnO2 dispersion.
2. The method for preparing alcohol-soluble SnO2 according to claim 1, characterized in that: The ligands in S1 are organic amines with carbon chain numbers of 6-18, organic acids, and organic amines with hydroxyl groups.
3. The method for preparing alcohol-soluble SnO2 according to claim 1, characterized in that: The first solvent described in S1 refers to a solvent whose boiling point is lower than the reaction temperature of the system, and the second solvent refers to a solvent whose boiling point is higher than the reaction temperature of the system.
4. The method for preparing alcohol-soluble SnO2 according to claim 1, characterized in that: In S1, the ratio of the tin salt to the ligand is 1:(0.1-10) according to the amount of substance.
5. The method for preparing alcohol-soluble SnO2 according to claim 1, characterized in that: The precipitant in S3 is one of methanol, ethanol, acetone and acetonitrile.
6. The method for preparing alcohol-soluble SnO2 according to claim 1, characterized in that: The good solvent in S3 is one of dichloromethane, chloroform, n-hexane, n-heptane, n-octane, toluene and xylene.
7. Alcohol-soluble SnO2 prepared by the preparation method according to any one of claims 1 to 6, characterized in that: Including SnO2 inorganic matter and organic ligands on the surface of SnO2 inorganic matter.
8. The alcohol-soluble SnO2 according to claim 7, characterized in that: The organic ligand is a hydroxycarboxylic acid compound with a carbon chain number of 2-9, and the weight of the organic ligand accounts for 3%-25% of the whole.
9. The alcohol-soluble SnO2 according to claim 7, characterized in that: The alcohol-soluble SnO2 has a particle size of 3-10 nm and a band gap of 3.6-4.0 eV.
10. A method for preparing a perovskite solar cell using alcohol-soluble SnO2 as an electron transport layer, characterized in that: first, a hole transport material is spin-coated on the ITO anode layer to form a hole transport layer, a perovskite solution is spin-coated on the hole transport layer serving as a carrier to form an absorption layer, an alcohol solution of SnO2 is spin-coated on the absorption layer, and an electron transport layer is formed after drying, and finally, an Au cathode electrode layer is evaporated and packaged to form a perovskite solar cell.
Citation Information
Patent Citations
Bulk heterojunction solar battery based on water / alcohol soluble polymer mixed cathode interfacial layer and preparation method thereof
CN107978678A
Perovskite solar cell and manufacturing method thereof
CN108110141A
Multifunctional Lewis base molecule modified high-stability perovskite solar cell
CN115915796A
Perovskite solar cell and preparation method thereof
CN116437672A
Solar cell and preparation method thereof
CN117998877A